Obstacles to learning speaking skills among non-Arabic speaking learners in Indonesia - Bahruddin, Uril; Mubaraq, Zulfi (JURNAL IJ-ATL, 2023)
The pinnacle of success in language learning is mastery of speaking skills, as weakness in speaking is weakness in the entire language. The research aims to (1) describe the types of obstacles in learning speaking skills among students at Maulana Malik Ibrahim University Malang, Indonesia, (2) find out the causes of these obstacles on students, (3) and find out the impact of these obstacles on students. This research used the qualitative approach and case study method, and collected data through personal interviews, field observation, and document analysis. Data analysis began with the process of collecting, sorting, and displaying it, then drawing conclusions from it. The results of this research are: First: The types of obstacles to learning speaking skills among university learners are represented by difficulty in pronouncing sounds, choosing vocabulary, and forming sentences. Second: The emergence of obstacles to learning speaking skills is due to internal reasons represented by lack of self-confidence, lack of rich vocabulary, lack of courage, and fear of making mistakes; and external reasons represented by the influence of the mother tongue, and the lack of a suitable Arabic environment. Third: The obstacles led to poor academic achievement, poor speaking skills, language anxiety, negative behavior when learning speaking skills, and negative perceptions of the Arabic language. The conclusion of the research indicates that the success of teaching and mastering speaking skills is achieved by overcoming all of these obstacles, stimulating motivation, and strengthening self-confidence.